Customer satisfaction of services offered by BUJ Technology Enterprise Sdn. Bhd / Nur Syahida Azma Mohd Yusoff - Mohd Yusoff, Nur Syahida Azma (2011)
This study explain customer satisfaction of services offered by BUJ Technology Enterprise. The objective was to identify the relationships between brand image, service quality and technology with the customer satisfaction and to determine what is the most influence variable between those three variables. This study used questionnaire which was distributed to 60 respondents from area Indera Mahkota, Semambu, Aspa Cottage, Sungai Lembing and Sungai Isap. The Statistical Package for the Social Sciences (SPSS) software was used to construct and analysed the data. The study found that brand image and technology influence with the customer satisfaction while service quality does not influence with the customer satisfaction. It also found that technology is the most influenced variable between those three variables. From the findings, researcher gave recommendation which can help BUJ Technology Enterprise to improve their brand image, service quality and technology. For brand image, it is suggested to BUJ Technology Enterprise build the message what are they trying to create about their company‟s value. Interm of service quality, BUJ Technology Enterprise must be consistence when they start their services. For technology, BUJ Technology Enterprise can use their latest technology which is Third generation garbage compactor in their waste collection services